The sensitivity of the redshift distribution to galaxy demographics. Issue 2 (23rd August 2022) - Sudek, Philipp; de la Bella, Lucia F; Amara, Adam; Hartley, William G
ABSTRACT: Photometric redshifts are commonly used to measure the distribution of galaxies in large surveys. However, the demands of ongoing and future large-scale cosmology surveys place very stringent limits on the redshift performance that are difficult to meet. A new approach to meet this precision need is forward modelling, which is underpinned by realistic simulations. In the work presented here, we use simulations to study the sensitivity of redshift distributions to the underlying galaxy population demographics. We do this by varying the redshift evolving parameters of the Schechter function for two galaxy populations: star-forming and quenched galaxies. Each population is characterized by eight parameters. We find that the redshift distribution of shallow surveys, such as the Sloan Digital Sky Survey (SDSS), is mainly sensitive to the parameters for quenched galaxies. However, for deeper surveys such as the Dark Energy Survey (DES) and the Hyper Suprime-Cam (HSC), the star-forming parameters have a stronger impact on the redshift distribution. Specifically, the slope of the characteristic magnitude, a M, for star-forming galaxies has overall the strongest impact on the redshift distribution. Decreasing a M by 148 per cent (its given uncertainty) shifts the mean redshift by ∼45 per cent. We explore which combination of colour and magnitude measurements is most sensitive to a M and we find that each colour–magnitude pair studied is similarly affected by a modification of a M .